Power control and rate management for wireless multimedia CDMA systems. - Chi Wan Sung
We consider a wireless multimedia code-division multiple-access system, in which the terminals transmit at different rates. We formulate the problem as a constrained optimization problem, with the objective of maximizing the total effective rate. An optimal power control strategy is derived. When the scale of the system is large, the optimal solution takes a simple form, which is easy to be applied practically. Furthermore, our basic model can be extended to include delay-sensitive traffic
Keywords: QoS; Code-division multiple-access system; Constrained optimization problem; Delay-sensitive traffic; Mobile communication systems; Optimal power control; Rate management; Single-cell CDMA system; Voice terminals; Wireless multimedia CDMA systems